Community-based trials of sexually transmitted disease treatment: repercussions for epidemiology and HIV prevention - Hudson Christopher P. (The World Health Organization, 2001)
This paper reviews the scientific basis for trials exploring the relation between sexually transmitted diseases (STDs) and human immunodeficiency virus (HIV) infection in Mwanza in the United Republic of Tanzania and Rakai and Masaka in the Republic of Uganda. The importance of a study?s location and explanations for the divergent results of these trials are discussed. The modest effect on STDs seen in the trial of syndromic management in Mwanza, in contrast to the 38% reduction in the incidence of HIV, casts doubt on the underlying hypothesis that treating STDs alone slows the transmission of HIV-1. According to the Piot-Fransen model, the trial in Rakai, which offered treatment of STDs to all subjects irrespective of symptoms (??mass?? treatment), should have been more effective both in reducing the prevalence of STDs and the incidence of HIV. However, the Rakai trial was stopped because there was no difference in the incidence of HIV between the intervention and control arms. If Mwanza is seen as the trial that needs explaining, another paradigm becomes relevant. In rural East Africa, where all trials have been conducted, networks of concurrent sexual partnerships are a source of infection with both STDs and HIV. Because of their shorter latency periods, STDs may prompt attendance at a clinic before the early signs of HIV-1 infection appear. Part of the management of STDs is to recommend abstinence or the consistent use of condoms until treatment is completed. This recommendation may cover the earliest period of viraemia during primary HIV-1 infection. This paradigm appears to explain the results from Mwanza and Rakai, emphasizing behavioural aspects of syndromic management.